Factors XI and XII as Targets for New Anticoagulants - Weitz, Jeffrey I.; Fredenburgh, James C. (Frontiers in Medicine, 2017)
Compared with vitamin K antagonists, the direct oral anticoagulants (DOACs) are simpler to administer and are associated with less intracranial bleeding. Nonetheless, even with the DOACs, bleeding still occurs and many patients with atrial fibrillation fail to receive anticoagulant thromboprophylaxis because of the fear of bleeding. Therefore, there is an urgent need for safer anticoagulants. Recent investigations into the biochemistry of hemostasis and thrombosis have identified new targets for development of novel anticoagulants. Using data from complementary sources, including epidemiological studies and investigations in various animal models, the contact pathway has emerged as a potential mediator of thrombosis that plays a minor part in hemostasis. Consequently, factor (F) XII of the contact system and FXI in the intrinsic pathway have been identified as potentially safer targets of anticoagulation than thrombin or FXa. However, further studies are needed to identify which is the better target for the appropriate indication. This review highlights the evidence for focusing on FXI and FXII and examines the novel approaches directed at these new targets. These emerging strategies should address current unmet medical needs and provide new avenues by which to improve anticoagulant therapy by reducing the risk of bleeding.